(untitled) (Bioscience Journal, 2018)
Xylanase can hydrolyze xylan for reducing its anti-nutritional impact and improving nutrient availability, so obtaining suitable xylanase to degrade xylan is essential. Error-prone PCR and gene transformation were used in this study to obtain the ideal xylanase for degrading xylan effectively. The result showed that one mutant xylanase gene with high xylanase expression was obtained. After the mutant xylanase gene was connected with pGAPZÎ±A and transformed into Pichia pastoris (P. pastoris), the recombinant P. pastoris with mutant gene was found to produce higher xylanase activity (0.1480 U/mL) than that with the native xylanase gene (0.1360 U/mL) after 12 h incubation (p<0.05). The optimal temperature and pH of xylanase expressed by native and mutant genes were the same, i.e. 40°C and 5.50 (p<0.05). In addition, adding 0.2% Tween 80 during recombinant P. pastoris incubation could significantly increase xylanase yield by about 30-35% (p<0.05). The mutant xylanase could significantly increase xylose yield from wheat meal more than the native xylanase (p<0.05).